THE EFFECTS OF CRUDE AQUEOUS AND ALCOHOL EXTRACTS OF ALOE VERA ON GROWTH AND ABDOMINAL VISCERA OF SUCKLING RATS - Beya, Wabeya; Davidson, Bruce; Erlwanger, Kennedy Honey (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The gastrointestinal tract of neonates is sensitive to dietary manipulations. When nursing mothers use Aloe vera, their babies are at risk of indirect exposure to Aloe vera via breast feeding or directly as health supplements. The effects of orally administered extracts of Aloe vera in unweaned rats were investigated. Six day old Sprague-Dawley rats were gavaged with aqueous or alcohol extracts of Aloe vera (low dose 50mg. kg-1 or high dose 500mg. kg-1) daily for eight days. All data were expressed as mean ± SD and analyzed by one way ANOVA. Pups receiving high doses of either extract had a significantly higher body mass gain than the group receiving lower dose (p < 0.05). Tibial length was significantly increased in the high dose aqueous extract group (15-26 %). The differences in growth could not be attributed to circulating insulin-like growth factor-1 as the levels were not significantly different. The caecum was significantly enlarged in the rats that received the high doses of both extracts. Although, there was no significant difference in the non-fasting plasma concentration of glucose and triglycerides, the hepatic lipid and glycogen content were significantly higher (p < 0.001) for the high dose aqueous extract group. The plasma alanine transaminase was not affected by the treatments, however the high doses of the extracts significantly increased plasma alkaline phosphatase activity. Short term administration of Aloe vera extracts resulted in growth promotion, enhanced hepatic storage of metabolic substrates, increased ALP possibly in relation to bone growth and caused hypertrophy of the caecum of neonatal rats. These effects need to be explored further to enhance animal production and health.